JUAL BELI TANAH ADAT ANTARA MASYARAKAT HUKUM ADAT DAYAK MAâANYAN DENGAN PERKEBUNAN KELAPA SAWIT DI KABUPATEN BARITO TIMUR PROVINSI KALIMANTAN TENGAH - , EKATNI PARUNA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purposes of this study are 1) to find out the mechanism of selling and purchasing the adat land with no ownershipcertificate in the adat law community of Dayak Maâayan, and 2) to analyze dispute resolution related to the sell and purchase of adat land in the adat law community of Dayak Maâayan. The study was conducted by using an empirical juridical approach with a qualitative method for data analysis. It was conducted in Paju Epat subdistrict, East Barito District, Central Borneo Province. Secondary data wereprimary legal materials, while primary ones were collected through interviews with respondents, including five people: Ario as a General Manager and Ramdhani as a Chairman of Human Resource Development in PT. Ketapang Subur Lestari as well as Uwei, Ranu, and Anci as representatives of adat law community of Dayak Maâanyan. Key informants of the studywere Bartherius as Damang (Chief of the adat law community) in Paju Epat subdistrict, East Barito District